Biological Influence of Nonswelling Microgels on Cartilage Induction of Mouse Adipose-Derived Stem Cells. (13th October 2019) - Liu, Zheng; Wang, Jun
Abstract : In cartilage tissue engineering, the target cells' functional performance depends on the biomaterials. However, it is difficult to develop an appropriate scaffold to differentiate mouse adipose-derived stem cells (mADSCs) into chondrocyte despite an increasing number of studies on biological scaffold materials. The purpose of this study was to create a novel scaffold for mADSC culture and chondrogenic differentiation with a new series of microgels based on polyethyleneimine (PEI), polyethylene glycol (PEG), and poly (L-lactic acid) (PLLA) and able to resist swelling with changes in temperature, pH, and polymer concentration. The biocompatibility and ability of the nonswelling microgels were then examined and served as scaffolds for cell culture and for cartilage differentiation. The results show that the new microgels are a novel biomaterial that both retains its nonswelling properties under various conditions and facilitates important scaffold functions such as cell adhesion, proliferation, and cartilage induction.